Site Effect Analysis in Prambanan District and Surroundings Using Shear Wave Velocity and Ellipticity Curve Method from Microtremor Data - Rahmania Sofyana Ulya, Rahmania Sofyana Ulya; Adhi, Mochamad Aryono; Budi Wibowo, Nugroho; Desi Mustami Limayukha, Desi Mustami Limayukha; Elsa Fadlika Widyantari, Elsa Fadlika Widyantari; Bilqis El Farsiyyi, Billqis El Farsiyyi; Ilqia Rahma, Ilqia Rahma (Universitas Negeri Semarang, 2023)
The shear wave velocity (Vs) is a crucial parameter for determining subsurface layers by averaging the Vs value to a depth of 30 meters, known as Vs30. This study aims to analyze the subsurface soil layers, calculate the Vs30 value, and assess the potential seismic site classifications in Kapanewon Prambanan and its surrounding areas. The research utilizes secondary microtremor data from 27 observation points in the form of MSD files. The microtremor data was processed using Geopsy software with the HVSR method to generate an H/V curve. This curve was further analyzed with the Ellipticity Curve method via Dinver software to obtain the Vs profile at various depths. The findings suggest that the subsurface layers in Kapanewon Prambanan are predominantly composed of hard, very dense soil, soft rocks, and solid rocks, based on the Vs30 values. The Vs30 distribution across the region ranges from 267.857 m/s to 1675.977 m/s, classified into site categories A, B, C, and D. However, the majority of the area falls under site classes B and C. These classifications indicate that the regions under B and C have a relatively lower potential for significant earthquake wave amplification. Nonetheless, attention should still be given to areas categorized under sites D and E, particularly for earthquake disaster mitigation efforts. This detailed Vs30 analysis provides critical insights for seismic assessments, regional planning, and mitigation strategies in Kapanewon Prambanan.